(untitled) (American Journal of Islam and Society, 2022)
The death of the 84-year-old scholar and activist AbdulHamid Ahmad AbuSulayman on August 18, 2021, marked the return to Allah of an influential thinker who, well-grounded in Islamic traditional thought, strove to address modern problems by historically- and contextually-aware applications of well-grounded Islamic principles. This essay seeks to present an intellectual overview of some of his most important work in a manner that honors the impact he has had on Islamic thought and on Muslim thinkers.